CONTENT AND FORMS OF TEACHING GERMAN IN KARAKALPAK GROUPS OF ACADEMIC LYCEUMS - Sadikova, A.B. (SCIENCE and SOCIETY, 2025)
The content of teaching students of Karakalpak groups of academic lyceums the German language is determined by various objective and subjective factors. The article compares the methods of teaching foreign languages currently used in lyceums. The author suggests the topic of the course, considers possible types of assignments and forms of conducting classes.